2009
DOI: 10.1016/j.otohns.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Early tracheotomy in elderly patients results in less ventilator‐associated pneumonia

Abstract: Early tracheotomy in elderly patients is associated with less ventilator-associated pneumonia, more frequent intubations, less total admission time, and a trend toward lower mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Tracheostomy reduces total mechanical ventilation time, shortens ICU and hospital stays, and is known to effectively reduce the occurrence of both pneumonia and hospital mortality. [1][2][3][4][5][6] A recent study examined the benefits of early tracheostomy, reporting that tracheostomy performed on stroke subjects within 1-3 d of intubation reduced ICU mortality, use of sedatives, and 6-month mortality. 7 In addition to these effects, another study reported that early tracheostomy in subjects who required postoperative mechanical ventilation following cardiac surgery effectively reduced hospital mortality, cardiac mortality, and the duration of ICU and hospital stays as compared with subjects who received late tracheostomy.…”
Section: Introductionmentioning
confidence: 99%
“…Tracheostomy reduces total mechanical ventilation time, shortens ICU and hospital stays, and is known to effectively reduce the occurrence of both pneumonia and hospital mortality. [1][2][3][4][5][6] A recent study examined the benefits of early tracheostomy, reporting that tracheostomy performed on stroke subjects within 1-3 d of intubation reduced ICU mortality, use of sedatives, and 6-month mortality. 7 In addition to these effects, another study reported that early tracheostomy in subjects who required postoperative mechanical ventilation following cardiac surgery effectively reduced hospital mortality, cardiac mortality, and the duration of ICU and hospital stays as compared with subjects who received late tracheostomy.…”
Section: Introductionmentioning
confidence: 99%
“…The abovestated relative risk of VAP onset, seen in our "T" and "non-T" ICU patients, represents a crude risk ratio, since data on the potential confounders in mechanically ventilated patients who did not develop VAP during ICU stay were not collected at this point. According to the literature, the incidence of VAP among tracheotomized patients varies from 6% to 26% 9,31,32 . However, many studies failed to specify the time elapsed between tracheotomy and VAP onset.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of tracheotomy on the development of VAP is not clearly defined. Some studies found decreases in VAP rates in patients having tracheotomy [6][7][8][9][10][11][12] , others have reported tracheotomy to be a risk factor favoring VAP onset [13][14][15][16][17][18][19][20] , while some could not demonstrate any VAP-related impact whatsoever [21][22][23][24] . Because of the conflicting literature data, there is currently no consensus on tracheotomy as either a VAP-protective or VAP-causative factor 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the use of tracheotomy procedures is ultimately increasing (10,11). Ventilator-associated pneumonia (VAP) is a common problem in patients on long-term mechanical ventilation in the ICU.…”
Section: Percutaneous Dilatational Tracheostomy (Pdt) Is Indicated Whmentioning
confidence: 99%
“…The risk factors are age greater than 60 years, multiple intubations, and even the tracheotomy itself. VAP incidence decreases when tracheotomies are performed earlier (11). All the components of the respiratory system are affected by aging, although at different rates; however, age in itself is not a risk factor of respiratory failure (12).…”
Section: Percutaneous Dilatational Tracheostomy (Pdt) Is Indicated Whmentioning
confidence: 99%